Do campo para o campo: a trajetória de uma educadora em busca da formação superior - SOUZA, Edna Lopes (2023)
This academic memoir constitutes an autobiographical narrative as a result of a survey of my life trajectory in the field and academically, describing the experiences acquired throughout my trajectory, considering that the facts presented deal with memories of this journey and the main collaborations for my development in my life. Its purpose is the differences between and the difficulties in schools in the rural area, and to present the perceptions in higher education, and the methodology applied in this study are memories referring to the life and educational trajectory presented by reports and actuarial photography, where they are visualized as results the perception of teaching methods and conclude their positive and negative character in the student's life depending on their application or absence. It also has a personal value because it will certainly add necessary knowledge to my training and actions carried out within the school, it will certainly add to my knowledge built throughout my academic career.